Wind tunnel test of the performance of coaxial rigid rotor - Wang, C.; Huang, M.Q.; Peng, X.; Zang, G.; Tang, M.; Wang, H. (My University, 2020)
Tests of 2m-diameter rigid coaxial rotor model were conducted in the?3.2m wind tunnel of CARDC to investigate the hovering and forward flight aerodynamic characteristics of rigid coaxial rotor. The aerodynamic data such as rotor lift, drag and power were acquired in the test, and the aerodynamic force of upper and lower rotor were measured individually. The hover test results show that the FM of the upper and lower rotors is lower than that of the isolated single rotor, and the FM of the lower rotor is lower than that of the upper rotor. Increasing lift offset will result in a decrease in the required power of the rotor and an increase in drag. When the effect of reducing power is greater than the effect of increasing drag, the lift-to-drag ratio of the rotor increases as the lift offset. In the forward flight state, the lift-to-drag ratios of the upper and lower rotors are smaller than the isolated single rotor. And the lift-drag ratio of the upper rotor is lower than that of the lower rotor, which is significantly different from the hover state.